Phytochrome and Ethylene Signaling Integration in Arabidopsis Occurs via the Transcriptional Regulation of Genes Co-targeted by PIFs and EIN3 - Jeong, Jinkil; Kim, Keunhwa; Kim, Mi E.; Kim, Hye G.; Heo, Gwi S.; Park, Ohkmae K.; Park, Youn-Il; Choi, Giltsu; Oh, Eunkyoo (Frontiers in Plant Science, 2016)
Plant seedlings germinating under the soil are challenged by rough soil grains that can induce physical damage and sudden exposure to light, which can induce photobleaching. Seedlings overcome these challenges by developing apical hooks and by suppressing chlorophyll precursor biosynthesis. These adaptive responses are respectively regulated by the phytochrome and ethylene signaling pathways via the PHYTOCHROME-INTERACTING FACTORs (PIFs) and the ETHYLENE INSENSITIVE 3 (EIN3)/EIN3-LIKE transcription factors. Although many processes downstream of phytochrome and ethylene signaling are similar, it remains unclear if and where these pathways converge. Here, we show PIFs and EIN3 induce similar changes in the transcriptome without robustly regulating each other’s signaling pathways. PIFs and EIN3 target highly overlapped gene promoters and activate subsets of the co-target genes either interdependently or additively to induce plant responses. For chlorophyll biosynthesis, PIFs and EIN3 target and interdependently activate the expression of HOOKLESS1. HOOKLESS1, in turn, represses chlorophyll synthesis genes to prevent photobleaching. Thus, our results indicate an integration of the phytochrome and ethylene signaling pathways at the level of transcriptional gene regulation by two core groups of transcription factors, PIFs and EIN3.